A TPE corner material with high bonding strength and preparation method thereof
By using a specific formula of TPE angle material in the joint material, combined with specific mixing and processing methods, the problem of insufficient shrinkage marks and joint strength in the process of joint material during the process is solved, and high joint strength, smooth surface and High processing efficiency effect.
Patent Information
- Application Number
- CN202410422568.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-04-09
AI Technical Summary
The existing scraps are prone to shrink marks and insufficient joint strength during processing, and the processing efficiency is low and the surface is not smooth and smooth.
A high bonding strength TPE joint angle material is used, and its formulation includes styrene-based elastomers, chlorinated polypropylene composites, tackifying resins, fillers, fillers, oils, polypropylene, lubricants, pigments, foaming agents and others Additives, through specific mixing and processing methods, improve the bonding strength and surface smoothness of the material.
It realizes the advantages of high bonding strength, smooth and smooth surface, no shrinkage marks and high processing efficiency, and improves the mechanical strength and shrinkage resistance of the finished jointing material.
Smart Images

Figure BDA0004782941380000101 
Figure BDA0004782941380000111 
Figure BDA0004782941380000112
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and more specifically, to a TPE corner material with high bonding strength and a preparation method thereof. Background Art
[0002] With the rapid development of social economy, people have an increasing demand for high-quality plastic materials. A large number of filler materials are used in the sealing strips of automobile bodies, doors, windows, engine hoods, trunks, etc. Currently, the filler materials on the market are mainly thermoplastic vulcanized rubber (TPV) filler materials and ethylene propylene diene monomer rubber (EPDM) filler materials.
[0003] EPDM takes a long time to process as a fillet material, and its structure is limited due to process reasons; TPV material has a short processing cycle and can be injection molded, but its bonding strength is insufficient and it is prone to shrinkage marks; while thermoplastic elastomer (TPE) material cures slower than TPV, has good bonding effect, and adjustable fluidity. In addition, TPE material has a low odor, simple processing technology, and low material cost.
[0004] However, TPE is often prone to the following problems when used as a corner material: First, due to the complexity of the corner mold and structure, while ensuring the bonding strength, shrinkage marks often appear on the surface, forming surface defects; second, when joining some EPDM guide grooves with more complex structures, the bonding strength is not as good as that of EPDM corner materials.
[0005] In the prior art, in order to solve the problem of shrinkage marks, injection molding plants often adopt the method of post-processing the mold and expanding the glue inlet to avoid shrinkage marks, but the appearance of the finished product will be different from the appearance of the original design; some injection molding plants adopt the method of externally mixing foaming agent before injection molding to reduce shrinkage marks, but the feeding uniformity of the externally mixed foaming agent is not good, and the volume of the corner material itself is small, which can easily cause the product to be unstable. The foaming agent is sensitive to temperature. The foaming temperature of conventional foaming agents is relatively low, usually in the range of 80-180°C, while the extrusion granulation temperature of conventional TPE materials is between 160-230°C. If integrated production is adopted in the general form, that is, the foaming agent is added to the corner material for direct extrusion granulation, the foaming agent will begin to foam during the extrusion granulation process of preparing the corner material, resulting in an extremely low retention rate of the foaming agent in the finished product. In order to solve the problem of joint strength, the addition of tackifying resin is generally used to improve it, but the corner structure and flow channel are relatively complex. The tackifying resin has a high viscosity, is not easy to flow, has a low softening point, and is not heat-resistant, which limits its application in corner materials. Some injection molding plants also use coating materials on the outer surface of injection molded parts to strengthen the joint strength in the later stage, but this greatly increases manpower and material resources, has low processing efficiency, and is prone to uneven coating for complex corner structures.
[0006] Therefore, how to prepare a new joint material that has the advantages of high joining strength, smooth surface, no shrinkage marks and high processing efficiency. Summary of the invention
[0007] In order to prepare a new corner material that has the advantages of high bonding strength, smooth surface, no shrinkage marks, and high processing efficiency, the present application provides a TPE corner material with high bonding strength and a preparation method thereof.
[0008] In the first aspect, the present application provides a TPE corner material with high bonding strength, adopting the following technical solution: a TPE corner material with high bonding strength, comprising the following raw materials in parts by weight: 20-50 parts of styrene elastomer, 2-10 parts of chlorinated polypropylene compound, 2-15 parts of tackifying resin, 1-20 parts of filler, 10-50 parts of filling oil, 5-30 parts of polypropylene, 0.2-5 parts of lubricant, 1-4 parts of pigment, 0.1-10 parts of foaming agent, and 1-5 parts of other additives.
[0009] By adopting the above technical scheme, the styrene elastomer makes the corner material have better mechanical properties; with the compatible combination effect of chlorinated polypropylene and polypropylene, the chlorinated polypropylene can penetrate into the polypropylene, so that the two polymer molecules of chlorinated polypropylene and polypropylene are entangled and folded with each other, and the introduction of chlorine greatly increases the active sites of polypropylene for chemical reaction, thereby improving the bonding strength of the corner material; and the chlorinated polypropylene can also improve the compatibility of polypropylene with thickening resin, elastomer and thickening resin, improve the structural density and bonding stability between the raw materials inside the corner material, thereby improving the mechanical strength of the corner material; with the foaming effect of the foaming agent, the shrinkage problem of the corner material can be alleviated, and with the filling effect of the filler, the shrinkage problem can be further buffered, so that the corner material is not easy to produce shrinkage marks; with the lubricating and dispersing effect of the lubricant and the filling oil, the processing performance of the material can be improved, and the smoothness of the surface of the corner material can be improved; so that the finished corner material has the advantages of high bonding strength, smooth surface, no shrinkage marks and high processing efficiency.
[0010] Preferably, the chlorinated polypropylene composite is composed of chlorinated polypropylene and maleic anhydride grafted modified chlorinated polypropylene in a mass ratio of 1:0.5-1.
[0011] By adopting the above technical solution, chlorinated polypropylene has high bonding compatibility with polypropylene and styrene elastomers, which can improve the bonding effect and structural density between the raw materials, thereby improving the bonding strength of the finished corner material.
[0012] Preferably, the styrene elastomer is one or more of SEBS, SBS, SIS, SEEPS and SEEP.
[0013] By adopting the above technical solution, the high elasticity and high resilience of SEBS, SBS, SIS, SEEPS and SEEP are utilized to give the corner material better elasticity and resilience, so that it can be used as a seal.
[0014] Preferably, the foaming agent is one or more of bicarbonate, azodicarbonamide, and diisopropyl azodicarboxylate.
[0015] By adopting the above technical scheme, bicarbonate, azodicarbonamide and diisopropyl azodicarboxylate can produce foaming expansion in styrene elastomers by generating gas foaming when heated to alleviate the post-shrinkage problem of elastic components. The presence of small molecular bubbles is not easy to affect the strength and service life of the finished material, and combined with the supporting effect of the filler, support is generated near the bubbles, thereby ensuring the strength and toughness of the corner material.
[0016] Preferably, the polypropylene is one or more of homopolymer polypropylene, copolymer polypropylene and block copolymer polypropylene.
[0017] By adopting the above technical scheme, the homopolymer polypropylene, copolymer polypropylene and block copolymer polypropylene are matched to ensure the strength of the finished corner material. Combined with the toughness of the elastomer and the bonding effect of the tackifying resin on the filler, polypropylene and chlorinated polypropylene, the internal structure density of the corner material is further improved, thereby improving the strength of the corner material and extending the service life of the corner material.
[0018] Preferably, the foaming agent is coated azodicarbonamide; the coated azodicarbonamide is prepared from azodicarbonamide, maleic anhydride grafted EVA and shellac film in a mass ratio of 1:0.1-0.25:0.2-0.4.
[0019] By adopting the above technical scheme, azodicarbonamide, maleic anhydride grafted EVA and shellac film are matched, and the barrier effect of the shellac film is utilized to prevent azodicarbonamide from absorbing moisture and affecting the molding effect and mechanical properties of the corner material; as the processing temperature increases, the shellac film gradually melts and flows, and the good compatibility of maleic anhydride grafted EVA with chlorinated polypropylene, polypropylene and styrene elastomers is combined to promote the foaming agent to be located on the surface of styrene elastomers, polypropylene and other materials. When shrinkage problems occur in styrene elastomers, polypropylene and other materials, the foaming effect can be utilized to fill the surrounding pores, thereby avoiding the generation of shrinkage marks.
[0020] Azodicarbonamide, maleic anhydride grafted EVA and shellac film are matched. During the raw material mixing process, the surface of the shellac film is relatively smooth, which is convenient for uniform dispersion and mixing of the raw materials. As the temperature rises, the shellac film gradually melts, and the viscosity of the shellac film gradually increases after hot melting, which is convenient for bonding to the surface of the material in contact with it. As the maleic anhydride grafted EVA is gradually exposed, the good compatibility and bonding effect of styrene elastomers, polypropylene, chlorinated polypropylene and maleic anhydride grafted EVA is utilized to make azodicarbonamide adhere to the surface of styrene elastomers, polypropylene and chlorinated polypropylene, and the amide group and the hydroxyl group in the shellac cooperate to further improve the cross-linking bonding, thereby improving the density of the internal structure while improving the strength and shrinkage resistance of the finished corner material.
[0021] Preferably, the tackifying resin is composed of hydrogenated rosin resin, polypropylene wax modified tetrapod-shaped zinc oxide whiskers and silicone powder in a mass ratio of 1:0.1-0.2:0.05-0.1.
[0022] By adopting the above technical scheme, hydrogenated rosin resin, polypropylene wax, modified four-needle zinc oxide whisker and silicone powder are matched, and the bonding effect of polypropylene wax is used to facilitate the bonding of polypropylene wax modified four-needle zinc oxide whisker to the surface of hydrogenated rosin resin, and the lubricating effect of silicone powder is used to make the tackifying resin have better dispersion uniformity during the raw material mixing process; and as the temperature rises during the processing process, the polypropylene wax on the surface of the four-needle zinc oxide whisker gradually melts and flows, and the good lubricity of polypropylene wax is used in combination with the multi-directional whisker structure on the surface of the four-needle zinc oxide whisker to play a drainage role for the multi-directional flow of hydrogenated rosin resin, thereby facilitating the hydrogenated rosin resin to move to various positions in all directions while also having a certain lubricating effect, and not easily affecting the fluidity due to viscosity increase, thereby ensuring that raw materials such as styrene elastomers and tackifying resins can evenly flow to various edge positions in a complex mold, ensuring the molding filling effect of the loaded corner material, and making it difficult for the loaded corner material to affect the fluidity due to over-stickiness, resulting in no filling at the edge position of the complex structure.
[0023] By utilizing the compatible bonding effect of polypropylene wax with polypropylene and chlorinated polypropylene, the bonding effect between alumina fiber and styrene elastomers, tackifying resins, polypropylene, chlorinated polypropylene and other raw materials is further improved. The better strength of polypropylene and zinc oxide fibers is combined to ensure the mechanical strength of the corner material. The flexibility of zinc oxide fibers and the elasticity of styrene elastomer are combined to ensure the impact strength of the corner material.
[0024] Preferably, the filler is modified talc; the modified talc is composed of talc, rosin resin and maleic anhydride grafted SEBS in a mass ratio of 1:0.05-0.2:0.1-0.3.
[0025] By adopting the above technical scheme, talcum powder, rosin resin, and maleic anhydride grafted SEBS are matched, and the good compatibility and adhesion of maleic anhydride grafted SEBS with styrene elastomers are utilized to improve the bonding effect between fillers and styrene elastomers, polypropylene, chlorinated polypropylene and other materials, thereby improving the density of the internal structure of the corner material and improving the strength and impact resistance of the corner material.
[0026] Rosin resin is soluble in oil solvents. During the processing, as the temperature gradually increases, the dissolution of rosin resin is accelerated, so that talcum powder can be more stably bonded to the inside of the filler. Combined with the lubricating effect of talcum powder itself, the uniform dispersion of filler is guaranteed. In addition, the tackifying resin and rosin resin cooperate to further increase the bonding strength of the filler. It makes it difficult for the filler to produce shrinkage marks during the preparation process, and has a higher bonding strength after preparation.
[0027] Preferably, the filler oil is composed of white oil and molecular sieve in a mass ratio of 1:0.05-0.15.
[0028] By adopting the above technical scheme, white oil and molecular sieve are matched, and white oil can promote the hot melting of SEBS in styrene elastomer, increase the fluidity of SEBS, improve the processing performance, and can adjust the hardness of SEBS and PP blend according to the hardness of the bonding material, thereby improving the applicability of the bonding material; the porous structure inside the molecular sieve is used to facilitate the adsorption of filling oil. Since the filling oil is in uniform contact with the styrene elastomer and the foaming agent is in contact with the styrene elastomer, after the foaming agent generates bubbles, the pore structure in the molecular sieve can provide a circulation space for the gas, which can avoid the gas from forming a continuous channel in the corner material, so as to prevent the continuous channel from reducing the strength of the bonding material and the uneven appearance.
[0029] In a second aspect, the present application provides a method for preparing a TPE corner material with high bonding strength, using the following technical solution:
[0030] A method for preparing a TPE corner material with high bonding strength comprises the following steps:
[0031] S1. Weigh styrene elastomer, chlorinated polypropylene compound, tackifying resin, filler, filler oil, polypropylene, pigment, foaming agent, lubricant, and other additives;
[0032] S2, blending the extended oil with the styrene elastomer for 3-8 minutes, and letting it stand for 25-35 minutes to obtain an oil-extended styrene elastomer, which are respectively recorded as extended oil material 1 and extended oil material 2 according to a mass ratio of 8-9:1;
[0033] S3, blending the oil-filled material 1, the chlorinated polypropylene compound, the tackifying resin, the filler, the polypropylene, the pigment, the lubricant, and other additives for 3-8 minutes, and mixing them thoroughly to obtain a mixture 1;
[0034] S4, mixing the oil-filled material 2 and the foaming agent uniformly to obtain a mixed material 2;
[0035] S5. Feed the mixed material 1 through the main feeding port with a temperature of 200-220° C., feed the mixed material 2 through the side feeding port with a temperature of 145-155° C., and granulate the mixed material by extrusion to obtain TPE corner material particles.
[0036] By adopting the above technical scheme, the high-temperature shear process from the main feed to the side feed port ensures that the material can be plasticized evenly. When the foaming agent is added to the side feeder, the foaming agent does not participate in the high-temperature and high-shear process, ensuring that the side feeder performs low-temperature and low-shear after the foaming agent is put into the side feeder. The foaming agent is not easy to foam during the extrusion process, ensuring the retention rate of the foaming agent; the foaming agent can also be evenly mixed with other raw materials to achieve one-step foaming, thereby improving the processing efficiency and ensuring the effective retention rate of the foaming agent; and during the later injection molding of the material, the foaming agent reacts to complete the foaming, reducing the generation of shrinkage marks while making the surface of the finished material smooth and flat.
[0037] In summary, this application has the following beneficial effects:
[0038] 1. Styrene elastomer, chlorinated polypropylene and polypropylene are matched. Since chlorinated polypropylene can penetrate into polypropylene, the two polymer molecules of chlorinated polypropylene and polypropylene are entangled and folded with each other, and the introduction of chlorine greatly increases the active sites of polypropylene for chemical reaction, thereby improving the bonding strength of the corner material; chlorinated polypropylene, polypropylene and tackifying resin are matched to improve the structural density and bonding stability between the raw materials inside the corner material, thereby improving the mechanical strength of the corner material; the foaming effect of the foaming agent can alleviate the shrinkage problem of the corner material, and the filling effect of the filler can further buffer the shrinkage problem, making it difficult for the corner material to produce shrinkage marks; the lubricating and dispersing effect of the lubricant and filling oil can improve the processing performance of the material and the smoothness of the surface of the corner material; so that the finished corner material has the advantages of high bonding strength, smooth surface, no shrinkage marks and high processing efficiency.
[0039] 2. Azodicarbonamide, maleic anhydride grafted EVA and shellac film are matched. During the raw material mixing process, the surface of the shellac film is relatively smooth, which is convenient for uniform dispersion and mixing of the raw materials. As the temperature rises, the shellac film gradually melts, and the viscosity of the shellac film gradually increases after hot melting, which is convenient for bonding to the surface of the material in contact with it. As the maleic anhydride grafted EVA is gradually exposed, the good compatibility and bonding effect of styrene elastomers, polypropylene, chlorinated polypropylene and maleic anhydride grafted EVA is utilized to make azodicarbonamide adhere to the surface of styrene elastomers, polypropylene and chlorinated polypropylene, and the amide group and the hydroxyl group in the shellac cooperate to further improve the cross-linking bonding, thereby improving the density of the internal structure while improving the strength and shrinkage resistance of the finished corner material.
[0040] 3. Utilize the compatible bonding effect of polypropylene wax with polypropylene and chlorinated polypropylene to further improve the bonding effect between alumina fiber and styrene elastomers, tackifying resins, polypropylene, chlorinated polypropylene and other raw materials. Combined with the better strength of polypropylene and zinc oxide fiber, the mechanical strength of the corner material is guaranteed. Combined with the flexibility of zinc oxide fiber and the elasticity of styrene elastomer, the impact strength of the corner material is guaranteed. DETAILED DESCRIPTION
[0041] The present application is further described in detail below with reference to the embodiments.
[0042] Preparation Example of Coated Azodicarbonamide
[0043] The shellac among the following raw materials was purchased from Shanghai Enzyme-Linked Biotechnology Co., Ltd.; maleic anhydride grafted EVA was purchased from Guangzhou Jinzhou Chemical Co., Ltd., with a melting point of 71°C; other raw materials and equipment were all commercially available.
[0044] Preparation Example 1: Coated azodicarbonamide was prepared by the following method:
[0045] The maleic anhydride grafted EVA is heated to 85°C until it is completely melted to obtain an EVA liquid;
[0046] Weigh shellac and heat it to 120℃ to completely melt it to obtain shellac liquid;
[0047] 0.2 kg of maleic anhydride grafted EVA liquid was evenly sprayed on the surface of 1 kg of azodicarbonamide, and then 0.3 kg of shellac liquid was evenly sprayed, and after drying and dispersion, the finished coated azodicarbonamide was obtained.
[0048] Preparation Example 2: This preparation example differs from Preparation Example 1 in that:
[0049] 0.1 kg of maleic anhydride grafted EVA liquid was evenly sprayed on the surface of 1 kg of azodicarbonamide, and then 0.2 kg of shellac liquid was evenly sprayed, and after drying and dispersion, the finished coated azodicarbonamide was obtained.
[0050] Preparation Example 3: This preparation example differs from Preparation Example 1 in that:
[0051] 0.25 kg of maleic anhydride grafted EVA liquid was evenly sprayed on the surface of 1 kg of azodicarbonamide, and then 0.4 kg of shellac liquid was evenly sprayed, and after drying and dispersion, the finished coated azodicarbonamide was obtained.
[0052] Preparation Example of Tackifying Resin
[0053] Among the following raw materials, hydrogenated rosin resin was purchased from Dongguan Yucheng Plastics Co., Ltd. with a softening point of 86°C; other raw materials and equipment were all commercially available.
[0054] Preparation Example 4: The tackifying resin is prepared by the following method:
[0055] Weigh 0.5 kg of polypropylene wax, heat and melt it, and then spray it evenly on the surface of 1 kg of four-needle zinc oxide whiskers, the average length of the four-needle zinc oxide whiskers is 10 μm, and then dry and disperse them to obtain polypropylene wax modified four-needle zinc oxide whiskers;
[0056] 1 kg of hydrogenated rosin resin and 0.15 kg of polypropylene wax modified four-needle zinc oxide whisker are mixed and stirred evenly, and the average particle size of the hydrogenated rosin resin is 20 μm; then the temperature is raised to 100° C., and the mixing and stirring is continued. Then 0.08 kg of silicone powder is evenly sprayed, and the average particle size of the silicone powder is 5 μm. After mixing evenly, cooling and dispersing, a finished tackifying resin is obtained.
[0057] Preparation Example 5: This preparation example differs from Preparation Example 4 in that:
[0058] 1 kg of hydrogenated rosin resin and 0.1 kg of polypropylene wax modified tetrapod-shaped zinc oxide whisker are mixed and stirred evenly, and the average particle size of the hydrogenated rosin resin is 20 μm; then the temperature is raised to 100° C., the mixing and stirring is continued, and then 0.05 kg of silicone powder is evenly sprayed, and the average particle size of the silicone powder is 5 μm. After mixing evenly, cooling and dispersing, a finished tackifying resin is obtained.
[0059] Preparation Example 6: This preparation example differs from Preparation Example 4 in that:
[0060] 1 kg of hydrogenated rosin resin and 0.2 kg of polypropylene wax modified four-needle zinc oxide whisker are mixed and stirred evenly, and the average particle size of the hydrogenated rosin resin is 20 μm; then the temperature is raised to 100° C., the mixing and stirring is continued, and then 0.1 kg of silicone powder is evenly sprayed, and the average particle size of the silicone powder is 5 μm. After mixing evenly, cooling and dispersing, a finished tackifying resin is obtained.
[0061] Preparation example of modified talc
[0062] Among the following raw materials, maleic anhydride grafted SEBS was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.; other raw materials and equipment were commercially available.
[0063] Preparation Example 7: Modified talcum powder is prepared by the following method:
[0064] Weigh rosin resin and heat it until it softens and melts to obtain rosin resin liquid;
[0065] 0.1 kg of rosin resin liquid is evenly applied on the surface of 1 kg of talc powder, the average particle size of the talc powder is 20 μm, and then 0.2 kg of maleic anhydride grafted SEBS is evenly sprayed, mixed evenly, cooled and dispersed to obtain the finished modified talc powder.
[0066] Preparation Example 8: This preparation example differs from Preparation Example 7 in that:
[0067] 0.05 kg of rosin resin liquid is evenly applied on the surface of 1 kg of talc powder, and then 0.1 kg of maleic anhydride grafted SEBS is evenly sprayed, mixed evenly, cooled and dispersed to obtain the finished modified talc powder.
[0068] Preparation Example 9: This preparation example differs from Preparation Example 7 in that:
[0069] 0.2 kg of rosin resin liquid is evenly applied on the surface of 1 kg of talc powder, and then 0.3 kg of maleic anhydride grafted SEBS is evenly sprayed, mixed evenly, cooled and dispersed to obtain the finished modified talc powder.
[0070] Preparation example of filler oil
[0071] Preparation Example 10: The filler oil is prepared by the following method:
[0072] Weigh 1 kg of white oil and 0.1 kg of molecular sieve, the porosity of the molecular sieve is 35-40%, the adding speed of the molecular sieve is 30 g / min, the stirring speed of the white oil is 120 r / min, mix them evenly, and obtain filling oil.
[0073] Preparation Example 11: This preparation example differs from Preparation Example 10 in that:
[0074] Weigh 1 kg of white oil and 0.05 kg of molecular sieve, add the molecular sieve at a rate of 30 g / min, stir the white oil at a rate of 120 r / min, mix them evenly, and obtain filling oil.
[0075] Preparation Example 12: This preparation example differs from Preparation Example 10 in that:
[0076] Weigh 1 kg of white oil and 0.15 kg of molecular sieve, add the molecular sieve at a rate of 30 g / min, stir the white oil at a rate of 120 r / min, mix them evenly, and obtain filler oil.
[0077] Example
[0078] The chlorinated polypropylene among the following raw materials was purchased from Shandong Ketian Chemical Co., Ltd., maleic acid grafted modified chlorinated polypropylene was purchased from HARDLEN and F-2P of Toyobo of Japan; homopolymer polypropylene, copolymer polypropylene and block copolymer polypropylene in polypropylene were all purchased from Shanghai Chaoqi Plastic Chemical Co., Ltd. and Exxon Polypropylene; styrene elastomers were SEBS, SBS and SIS of Yueyang Xingchang Petrochemical Co., Ltd.; other raw materials and equipment were commonly available on the market.
[0079] Example 1: A TPE corner material with high bonding strength:
[0080] 40kg styrene elastomer, 8kg chlorinated polypropylene compound, 8kg tackifying resin, 10kg filler, 30kg filling oil, 20kg polypropylene, 3kg lubricant, 2kg pigment, 5kg foaming agent, 2kg other additives; the styrene elastomer is SEBS; the chlorinated polypropylene compound is composed of chlorinated polypropylene and maleic anhydride grafted modified chlorinated polypropylene in a mass ratio of 1:1; the tackifying resin is hydrogenated rosin resin; the filler is talcum powder; the filling oil is white oil; the polypropylene is homopolymer polypropylene; the lubricant is erucamide; the pigment is carbon black; the foaming agent is azodicarbonamide; the other additives are composed of antioxidant 1010 and light stabilizer 770 in a mass ratio of 1:1;
[0081] The preparation method is as follows:
[0082] S1. Weigh the styrene elastomer, chlorinated polypropylene compound, tackifying resin, filler, filler oil, polypropylene, pigment, foaming agent, lubricant, and other additives according to the above weight;
[0083] S2, blending the extended oil with the styrene elastomer for 5 minutes, and letting it stand for 30 minutes to obtain an oil-extended styrene elastomer, which are respectively recorded as extended oil material 1 and extended oil material 2 according to a mass ratio of 9:1;
[0084] S3, blending the oil-filled material 1, the chlorinated polypropylene compound, the tackifying resin, the filler, the polypropylene, the pigment, the lubricant, and other additives for 5 minutes, and mixing them thoroughly to obtain a mixture 1;
[0085] S4, mixing the oil-filled material 2 and the foaming agent uniformly to obtain a mixed material 2;
[0086] S5. Discharge mixed material 1 through the main feeding port and discharge mixed material 2 through the side feeding port. The temperature of the main feeding zone of the twin screw is 210°C, the main engine stirring speed is 400r / min, the main feeding speed is 30kg / h, the side feeding temperature zone is 150°C, the side feeding speed is 2kg / h, the extrusion temperature is 140°C, and after extrusion granulation, TPE corner material particles are obtained.
[0087] Embodiment 2: This embodiment differs from Embodiment 1 in that:
[0088] 20kg styrene elastomer, 2kg chlorinated polypropylene compound, 2kg tackifying resin, 1kg filler, 10kg filling oil, 5kg polypropylene, 0.2kg lubricant, 1kg pigment, 0.1kg foaming agent, 1kg other additives; the styrene elastomer is SBS; the chlorinated polypropylene compound is composed of chlorinated polypropylene and maleic anhydride grafted modified chlorinated polypropylene in a mass ratio of 1:0.5; the tackifying resin is phenolic resin; the filler is calcium carbonate; the filling oil is paraffin oil; the polypropylene is copolymerized polypropylene; the lubricant is zinc stearate; the pigment is carbon black; the foaming agent is ammonium bicarbonate;
[0089] During the preparation process:
[0090] S2, blending the extended oil with the styrene elastomer for 3 minutes, and letting it stand for 35 minutes to obtain an oil-extended styrene elastomer, which are respectively recorded as extended oil material 1 and extended oil material 2 according to a mass ratio of 8:1;
[0091] S3, blending the oil-filled material 1, the chlorinated polypropylene compound, the tackifying resin, the filler, the polypropylene, the pigment, the lubricant, and other additives for 3 minutes, mixing them thoroughly to obtain a mixture 1.
[0092] Embodiment 3: This embodiment differs from Embodiment 1 in that:
[0093] 50kg styrene elastomer, 10kg chlorinated polypropylene compound, 15kg tackifying resin, 20kg filler, 50kg filler oil, 30kg polypropylene, 5kg lubricant, 4kg pigment, 10kg foaming agent, 5kg other additives; the styrene elastomer is SIS; the chlorinated polypropylene compound is composed of chlorinated polypropylene and maleic anhydride grafted modified chlorinated polypropylene in a mass ratio of 1:1; the filler is wollastonite; the filler oil is white oil; the polypropylene is block copolymer polypropylene; the lubricant is paraffin; the pigment is carbon black; the foaming agent is diisopropyl azodicarboxylate;
[0094] During the preparation process:
[0095] S2, blending the extended oil with the styrene elastomer for 8 minutes, and letting it stand for 25 minutes to obtain an oil-extended styrene elastomer, which are respectively recorded as extended oil material 1 and extended oil material 2 according to a mass ratio of 9:1;
[0096] S3, blending the oil-filled material 1, the chlorinated polypropylene compound, the tackifying resin, the filler, the polypropylene, the pigment, the lubricant, and other additives for 8 minutes, mixing them thoroughly to obtain a mixture 1.
[0097] Embodiment 4: This embodiment differs from Embodiment 1 in that:
[0098] The foaming agent is the coated azodicarbonamide prepared in Preparation Example 1; the tackifying resin is the tackifying resin prepared in Preparation Example 4; the filler is the modified talc prepared in Preparation Example 7; and the filler oil is the filler oil prepared in Preparation Example 10.
[0099] Embodiment 5: This embodiment differs from Embodiment 4 in that:
[0100] The foaming agent is the coated azodicarbonamide prepared in Preparation Example 2; the tackifying resin is the tackifying resin prepared in Preparation Example 5; the filler is the modified talc prepared in Preparation Example 8; and the filler oil is the filler oil prepared in Preparation Example 11.
[0101] Embodiment 6: This embodiment differs from Embodiment 4 in that:
[0102] The foaming agent is the coated azodicarbonamide prepared in Preparation Example 3; the tackifying resin is the tackifying resin prepared in Preparation Example 6; the filler is the modified talc prepared in Preparation Example 9; and the filler oil is the filler oil prepared in Preparation Example 12.
[0103] Embodiment 7: This embodiment differs from Embodiment 4 in that:
[0104] No maleic anhydride grafted EVA and shellac film were added during the preparation of the coating foaming agent.
[0105] Embodiment 8: This embodiment differs from Embodiment 4 in that:
[0106] No silicone powder was added during the preparation of the tackifying resin.
[0107] Embodiment 9: This embodiment differs from Embodiment 4 in that:
[0108] No polypropylene wax-modified tetrapod-shaped zinc oxide whiskers were added during the preparation of the tackifying resin.
[0109] Embodiment 10: This embodiment differs from Embodiment 4 in that:
[0110] The tetrapod-shaped zinc oxide whiskers modified with polypropylene wax are replaced with columnar zinc oxide fibers of equal mass in the tackifying resin.
[0111] Embodiment 11: This embodiment differs from Embodiment 4 in that:
[0112] Modified talcum powder does not contain rosin resin.
[0113] Embodiment 12: This embodiment differs from Embodiment 4 in that:
[0114] No molecular sieves are added to the filler oil.
[0115] Comparative Example
[0116] Comparative Example 1: The difference between this comparative example and Example 1 is that:
[0117] No chlorinated polypropylene compounds are added to the raw materials.
[0118] Performance testing
[0119] 1. Bonding strength test
[0120] The preparation methods of Examples 1-12 and Comparative Example 1 were used to prepare the corner materials respectively. The same EPDM material was joined using a vertical injection molding machine to make corner samples. The samples were referenced to the GB / T 528-2009 standard. The tensile strength of the joint was tested at a speed of 500 mm / min and the data was recorded.
[0121] 2. Surface inspection
[0122] Finished corner materials were prepared by the preparation methods of Examples 1-10 and 12, respectively, and the surface smoothness was scored, with high smoothness 10 points → roughness 1 point;
[0123] And the surface shrinkage marks are detected and the shrinkage area per unit area is recorded;
[0124] Perform filling inspection on the edge of the loaded mold and record the remaining gaps.
[0125] 3. Flow rate detection
[0126] Finished corner materials were prepared by the preparation methods of Examples 1-10 respectively, and the melt mass flow rate was tested with reference to GB / T 3682.1 / 2-2018, at a temperature of 230° C. and a load of 5 kg, and the data were recorded.
[0127] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data)
[0128]
[0129]
[0130] 4. Strength detection
[0131] Finished corner materials were prepared by the preparation methods of Examples 1-12 and Comparative Example 1, respectively. The 100% tensile stress-vertical direction, tensile strength (vertical direction), and elongation at break (vertical direction) were tested with reference to GB / T 528-2009, and the tensile speed was 500 mm / min, and the data were recorded. The compression permanent deformation was tested with reference to GB / T 7759.1-2015, the temperature was 23° C., the test time was 72 h, the compression rate was 25%, and the data were recorded. The hardness was tested with reference to GB / T 531.1-2008 (rubber), the reading time was 10 s, and the data were recorded.
[0132] 5. Friction test
[0133] Finished corner materials were prepared by the preparation methods of Examples 1 to 3 respectively, and the dynamic friction coefficient was tested with reference to GB / T 21282-2007, and the data were recorded.
[0134] Table 2 Performance Test Table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data)
[0135]
[0136] It can be seen from Examples 1-3 and Tables 1 and 2 that the corner material prepared in the present application has high bonding strength, a smooth surface, no shrinkage marks, high mechanical strength, high toughness, friction resistance, and good fluidity after hot melting.
[0137] Combining Example 1 and Examples 4-6 with Tables 1 and 2, it can be seen that the surface-treated tackifying resin, filler, filling oil, foaming agent and other substances can be well filled at the edge of the complex mold without filling gaps, and the bonding strength and mechanical strength are increased.
[0138] Combining Example 4 and Examples 7-12 and Tables 1 and 2, it can be seen that maleic anhydride grafted EVA and shellac film were not added during the preparation of the coated foaming agent in Example 7. Compared with Example 4, the bonding strength of Example 7 is lower than that of Example 4, the filling gap is larger than that of Example 4, and the strength is lower than that of Example 4. This indicates that the combination of maleic anhydride grafted EVA and shellac film can improve the bonding effect between the foaming agent and other raw materials, improve the structural density, and thus improve the strength. The shellac film has a certain smoothness, which improves the dispersion uniformity of the external foaming agent, thereby making the foaming agent evenly filled, thereby improving the bonding strength and mechanical strength of the finished corner material.
[0139] In the preparation process of the tackifying resin in Example 8, no silicone powder was added. Compared with Example 4, the bonding strength of Example 8 was lower than that of Example 4, the filling gap was larger than that of Example 4, and the strength was lower than that of Example 4. This indicates that the addition of silicone powder can increase the mixing uniformity of tackifying resin, polypropylene, chlorinated polypropylene, styrene elastomer and other materials during the mixing process, and facilitate the uniform filling of the corner material at the corners of the load mold.
[0140] In the preparation process of the tackifying resin of Example 9, no polypropylene wax-modified four-needle zinc oxide whisker was added. Compared with Example 4, the bonding strength of Example 9 was lower than that of Example 4, the filling gap was larger than that of Example 4, and the strength was lower than that of Example 4. This indicates that the polypropylene wax-modified four-needle zinc oxide whisker has a higher filling and reinforcing effect and a certain lubricating effect, thereby improving the strength and surface smoothness of the corner material, and is convenient for filling in the corners of the load mold, thereby improving the molding effect.
[0141] In Example 10, columnar zinc oxide fibers of equal mass are used to replace the polypropylene wax-modified four-needle zinc oxide whiskers in the tackifying resin. Compared with Example 4, the bonding strength of Example 10 is lower than that of Example 4, the filling gap is larger than that of Example 4, and the strength is lower than that of Example 4. This indicates that the combination of polypropylene wax and silicone powder can further improve the filling uniformity of the corner material at the edges and corners of complex molds, and improve the mechanical strength of the finished corner material.
[0142] The modified talcum powder of Example 11 is without adding rosin resin. Compared with Example 4, the bonding strength of Example 11 is lower than that of Example 4, the filling gap is larger than that of Example 4, and the strength is lower than that of Example 4. This shows that the addition of rosin resin can not only improve the bonding effect of each raw material and improve the strength, but also improve the joint strength and is not prone to shrinkage problems.
[0143] In Example 12, no molecular sieve is added to the filling oil. Compared with Example 4, the bonding strength of Example 12 is lower than that of Example 4, the filling gap is larger than that of Example 4, and the strength is lower than that of Example 4. This indicates that after the foaming agent generates bubbles, the pore structure in the molecular sieve can provide a circulation space for the gas, thereby ensuring the strength of the combined materials while ensuring the bonding strength of the corner materials.
[0144] Combining Example 1 and Comparative Example 1 and Tables 1 and 2, it can be seen that no chlorinated polypropylene is added to the raw materials of Comparative Example 1. Compared with Example 1, the bonding strength of Comparative Example 1 is lower than that of Example 1, indicating that chlorinated polypropylene can improve the bonding strength of the corner material.
[0145] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A TPE corner material with high bonding strength, characterized in that: The invention comprises the following raw materials in parts by weight: 20-50 parts of styrene elastomer, 2-10 parts of chlorinated polypropylene compound, 2-15 parts of tackifying resin, 1-20 parts of filler, 10-50 parts of filling oil, 5-30 parts of polypropylene, 0.2-5 parts of lubricant, 1-4 parts of pigment, 0.1-10 parts of foaming agent and 1-5 parts of other additives; the foaming agent is coated azodicarbonamide; the coated azodicarbonamide is prepared from azodicarbonamide, maleic anhydride grafted EVA and shellac film in a mass ratio of 1:0.1-0.25:0.2-0.4; the chlorinated polypropylene The composite material is composed of chlorinated polypropylene and maleic anhydride grafted modified chlorinated polypropylene in a mass ratio of 1:0.5-1; the tackifying resin is composed of hydrogenated rosin resin, polypropylene wax modified tetrapod-shaped zinc oxide whisker and silicone powder in a mass ratio of 1:0.1-0.2:0.05-0.1; the filler is modified talcum powder; the modified talcum powder is composed of talcum powder, rosin resin and maleic anhydride grafted SEBS in a mass ratio of 1:0.05-0.2:0.1-0.3; the filling oil is composed of white oil and molecular sieve in a mass ratio of 1:0.05-0.
15.
2. A TPE corner material with high bonding strength according to claim 1, characterized in that: The styrene elastomer is one or more of SEBS, SBS, SIS, SEEPS and SEEP.
3. A TPE corner material with high bonding strength according to claim 1, characterized in that: The foaming agent is one or more of bicarbonate, azodicarbonamide, and diisopropyl azodicarboxylate.
4. A TPE corner material with high bonding strength according to claim 1, characterized in that: The polypropylene is one or more of homopolypropylene and copolymer polypropylene.
5. A method for preparing a TPE corner material with high bonding strength according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Weigh styrene elastomer, chlorinated polypropylene compound, tackifying resin, filler, filler oil, polypropylene, pigment, foaming agent, lubricant, and other additives; S2, blending the extended oil with the styrene elastomer for 3-8 minutes, and letting it stand for 25-35 minutes to obtain an oil-extended styrene elastomer, which are respectively recorded as extended oil material 1 and extended oil material 2 according to a mass ratio of 8-9:1; S3, blending the oil-filled material 1, the chlorinated polypropylene compound, the tackifying resin, the filler, the polypropylene, the pigment, the lubricant, and other additives for 3-8 minutes, and mixing them thoroughly to obtain a mixture 1; S4, mixing the oil-filled material 2 and the foaming agent uniformly to obtain a mixed material 2; S5. Feed the mixed material 1 through the main feeding port with a temperature of 200-220° C., feed the mixed material 2 through the side feeding port with a temperature of 145-155° C., and granulate the mixed material by extrusion to obtain TPE corner material particles.
Citation Information
Patent Citations
Self-lubricating TPE corner connecting material with high bonding strength
CN113999481A